Medical Record Storage System Based on Accreditation Criteria 3.8.4 in Public Health Centers - Sri Wahyuningsih Nugraheni; Muhammad Amin bin Sahari; Beta Setiawati; Kufita Alya Salsabila (Global Health Science Group, 2022)
The Sawit Boyolali Community Health Center was accredited in 2017. Retention of medical record documents has been carried out in the last three years, namely 2020, 2021 and 2022. The obstacle in implementing retention is that there are no standard operating procedures regarding retention, storage systems and identification of medical records. This type of research is descriptive qualitative with a cross sectional research design. The research variable consists of three assessment elements on criteria 3.8.4. Collecting research data using interviews, observation and documentation. Processing, analysis and presentation of data is done descriptively. The results of the study are: the decree of the head of the public health center becomes the basis for the policy of implementing medical record retention without standard operating procedures, namely the decree of the head of the community health center Sawit Boyolali number 440 of 2017 concerning the storage of medical records. The implementation of medical record identification is regulated through standard operating procedures number 005/SOP/VII/UKP/2017 regarding patient registration. Medical record coding provides a medical record number code of eight digits, the first two digits are the village/kelurahan code, the second two digits are the medical record number, and the third two digits are the family card code/family status. The medical record storage system is centralized, that is, outpatient and inpatient medical records are stored in one folder/folder. Documentation of the results of examinations, treatment, actions, and other services that have been provided to patients by doctors, dentists and or health workers made immediately and after the patient receives services. The conclusions of the research based on accreditation criteria 3.8.4 are: (1) there is a retention policy in the form of a decree from the head of the public health center without standard operating procedures. Patient identification in medical records is regulated in standard operating procedures regarding patient registration. Medical record coding uses eight digits with a centralized storage system. Recording and documentation of medical records is carried out by the doctor in charge of the patient.